A proposed occupational safety and health management system model incorporating European foundation of quality management (EFQM) model - Abdul Aziz, Abdullah; Maysoon Shafeeq, Alremawi; Abdulmalek, A. Tambi (2019)
Despite the fact, that occupational accidents and resulting injuries and deaths sorely weaken human capital, and negatively influence the productivity and competitiveness of firms, there is a scarcity of preventive procedures and an absence of safety management systems among companies. Moreover, there is very little research done where the concept of Total Quality Management (TQM) as a business excellence strategy, which integrates the concept of occupational safety and health management system (OSHMS). This paper incorporates the concept of OSHMS within the perspective of TQM as a part of corporate culture in order to develop an OSHMS model through integrating OSHMS with the European Foundation of Quality Management (EFQM) Model, and define the critical factors for OSHMS excellence. The proposed model can be applied in different companies regardless of the size, maturity or sector. Study findings suggest that OSHMS model has a positive impact on people results, OSH performance, financial and non-financial performances. Therefore, deliver an evidence of the linkage between employees’ protection and organisation’s excellence. A better understanding of implementing OSHMS, and its enablers, will certainly support organizations to strategically deploy resources and concentrate efforts to develop their business performance and safety and health results.